Building safety index for elementary school building in West Sumatera. Issue 1 (May 2020) - Masril; Kurniawan, Deddy; Ismail, Mohammad
Abstract: Safety and health In building planning must be considered during the building service period. The research objective is the application of Safety Building Index (BSI) in elementary school building planning. The factors of previous research were six factors, and the authors assessed Seven, namely architectural factors, building services, the external environment, operational and maintenance, administration and management of building maintenance. The research method was carried out by distributing questionnaires then distributed to construction practitioners such as architects, engineers, surveyors, contractors, consultants and developers. After completing the questionnaire, form to carry out the analysis with the SPSS program. The results of statistical analysis reveal the highest level of influence of each building factor on building planning. The research findings are the influence of each of the factors reviewed and which factors are dominant. The most dominant factors that must be considered by planners in designing elementary school buildings so that the Building Safety index can be applied in elementary schools in West Sumatra Padang.